Information flow in excerpts of two translations of Mme Bovary - Sévigny, Alexandre (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article explores how information is accumulated and collated in a cog-nitively realistic fashion in two very short excerpts of translations of Flaubert ’s ‘Mme Bovary’. The approach taken is a formal cognitive linguistic one using Discourse Information Grammar (DIG), a theory of grammar based on the intuitive idea that texts are understood by the reader incrementally, in a left-to-right fashion. Thus, a cognitive pragmatic approach is taken to the study of the excerpts, highlighting how much information is accumulated as the reader develops an understanding of the text in question. The analysis discusses the differences in the build-up of information in the source text and in its translations. The conclusion indicates that translation studies contribute much to the development of formal linear cognitive linguistic theories.